1999
DOI: 10.1161/01.cir.100.15.1609
|View full text |Cite
|
Sign up to set email alerts
|

Intracoronary Thrombus and Platelet Glycoprotein IIb/IIIa Receptor Blockade With Tirofiban in Unstable Angina or Non–Q-Wave Myocardial Infarction

Abstract: for the PRISM-PLUS InvestigatorsBackground-The present study describes the effects of tirofiban, a nonpeptide platelet glycoprotein (GP) IIb/IIIa receptor blocker, on the characteristics of culprit lesions in patients with unstable angina (UA) or non-Q-wave myocardial infarction (NQWMI). Methods and Results-Of 1915 patients enrolled in PRISM-PLUS, 1491 had a readable film obtained a median of 65 hours after randomization. A core laboratory examined the culprit lesions for intracoronary thrombus burden (primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(59 citation statements)
references
References 37 publications
3
55
0
1
Order By: Relevance
“…26 The combination of a glycoprotein IIb ⁄ IIIa inhibitor plus heparin significantly reduces the intracoronary thrombus burden of the culprit lesions, improves the perfusion grade, and decreases the severity of the obstruction in patients with unstable angina or non-Q-wave MI. 27 We speculated that the association between use of glycoprotein IIb ⁄ IIIa inhibitors and shorter door-to-balloon time might originate from the facilitation in the clot dissolution, thereby hastening the passage of guide wires through the culprit lesions during PCI. Presentation at off-hours is a strong predictor of a prolonged door-to-balloon time in United States.…”
Section: Discussionmentioning
confidence: 99%
“…26 The combination of a glycoprotein IIb ⁄ IIIa inhibitor plus heparin significantly reduces the intracoronary thrombus burden of the culprit lesions, improves the perfusion grade, and decreases the severity of the obstruction in patients with unstable angina or non-Q-wave MI. 27 We speculated that the association between use of glycoprotein IIb ⁄ IIIa inhibitors and shorter door-to-balloon time might originate from the facilitation in the clot dissolution, thereby hastening the passage of guide wires through the culprit lesions during PCI. Presentation at off-hours is a strong predictor of a prolonged door-to-balloon time in United States.…”
Section: Discussionmentioning
confidence: 99%
“…15,16) Another recent randomized clinical trial, the PRISM-PLUS trial 17) demonstrated that the addition of tirofiban to heparin reduced the thrombus burden in the culprit lesion and improved distal perfusion in patients with unstable angina or non-Q-wave myocardial infarction. However, we could find no data on a combination of tirofiban and primary stenting for treatment of ST-segment elevated (ST-se) AMI.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it has been suggested that incremental antiplatelet therapy by GP IIb/IIIa receptor blockers might attenuate the formation of a new platelet-rich thrombus and thereby improve the outcome of primary PCI. 7,15,16) Recently, the PRISM-PLUS clinical trial 17) reported that the addition of tirofiban to heparin reduced the thrombus burden of the culprit lesion and improved distal perfusion in patients with unstable angina or non-Q-wave myocardial infarction. However, our present study demonstrated that compared with primary stenting alone, a combination therapy of early administration of tirofiban and primary stenting for treatment of ST-se AMI did not provide additional benefits for normal coronary blood flow in the IRA, in reducing major cardiac events 7,15,16,19,20) The short-term clinical outcomes of primary PCI have been improved by adjunctive pharmacologic therapy with abciximab.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…immediate (<6 hours) or early (≤72 hours). 3 Early CA with upstream glycoprotein (GP) IIb/IIIa inhibitors is associated with a reduction in intracoronary thrombus burden 4,5 and improvement in myocardial tissue-level perfusion. 6 On the other hand, immediate CA may reduce the bleeding risk related to GP IIb/IIIa inhibitor therapy, and in a randomized trial this strategy in the setting of non-ST-elevation ACS was associated with a better outcome.…”
Section: Introductionmentioning
confidence: 99%